Keterlibatan Penyandang Disabilitas dalam Pelayanan Publik di Era Society 5.0 - Sulistianingsih, Sulistianingsih (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2023)
The government encourages people with disabilities to participate as civil servants, through the policy of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 27 of 2021 concerning Procurement of Civil Servants (PNS). The involvement of people with disabilities in public services is strengthened by the Society 5.0 era, where technology is seen as a life support tool. This research aims to analyze the participation of people with disabilities as civil servants in the context of Society 5.0. The research method used is SWOT analysis (Strengths, Weakness, Opportunities and Threats). Implementation of policies regarding the procurement of civil servants in Indonesia has still not reached the target, in 2022 only 0.017% of people with disabilities will become civil servants from the targeted 2% quota. Based on this data, it is necessary to evaluate the involvement of people with disabilities as civil servants, whether the PANRB Ministerial Regulation Number 27 of 2021 has been implemented or not by the Ministries/Institutions and Regional Governments. The 2% representation of persons with disabilities must be maintained in the procurement of civil servants in the future, even if it is possible to increase the quota. Apart from that, it will be even more effective if this policy is followed by sanctions for Ministries/Institutions and Regional Governments that have not implemented the procurement of civil servants with disabilities.